The symbolic dimension of consumption and the market as a social construction: A study on home buying and the purchase of fashion products - Porcionato, Gabriela Lanza [UNESP]; Haddad, Beatriz Sumaya Malavasi [UNESP]; Castro, Ana Lúcia [UNESP]; Jardim, Maria Chaves [UNESP] (Universidade Federal de Goias, 2019)
Researches on the symbolic dimension of consumption and the concept of the market as social construction are issues addressed by two studies that, though carried out autonomously and with different themes, present convergence in the analysis.The objective of this article, therefore, is to reflect on these convergences. Thus, the first study analyzed is on the home purchase through the federal housing program, Minha Casa Minha Vida; and the second survey is on the consumption of global fashion brands in low-income communities. Both researches discuss the social relations that are established around the purchase of these goods, the rational discourses of the motivation of the purchase, and the consumption as a social and symbolic practice.
A dimensão simbólica do consumo e o mercado como construção social: um estudo sobre a compra da casa e de produtos de moda
Keywords: Assets; Belonging; Consumption; Market